BARRIERS TO AND STRATEGIES FOR SUSTAINABLE RELATIONSHIPS IN MULTILINGUAL CAMPUSES - Mambetaliev, Askar (Sustainable Multilingualism / Darnioji daugiakalbystė, 2023)
The article presents the dimensions of communication in multiethnic and multilingual education settings, the main barriers to sustainable relationships between students of different backgrounds and strategies to overcome those barriers. The main research question of the study is: What are the main barriers in sustainable relationships between students with different ethnic and linguistic backgrounds? A subsequent question is: How to overcome those barriers? Hence, the main goal of the article is to identify and address the main problems that undermine mutual understanding and collaborative learning among students. The method of the study is a literature review of the most significant studies and authors in the field. The goal is to present an analysis of their insights into the main problems of relationships between students on international campuses. The article is useful for campus leaders, students and mentors.